An integrative action research (IAR) on improving workforce planning in a technology company - Domingo, Anthony Ace R. (Animo Repository, 2022)
This action research aimed to address the high attrition rate of our employees by improving our project assignments guided by the skills matrix and project complexity to support the business growth of Company ABC Business Process Operations in the Philippines. Through the co-inquiry and effective collaborations with my collaborators, we discussed an array of issues attributed to the high attrition rate of our employees. My collaborators and I concentrated on how we can further improve our workforce planning and poor system for project assignment by addressing the absence of a database for skillset and non-existent project complexity. We identified hard and soft skills by revisiting our existing job descriptions to develop relevant benchmarks for the skills matrix. Furthermore, we used our internal “Technology Information Record” data to formulate our project complexity scoring and regroup our projects into simple, semi-complex, and complex. In the first cycle, guided by agile project management methodology, design thinking, and Information Technology Infrastructure Library (ITIL V4), we built a skill matrix and project complexity tool through Microsoft power apps and SharePoint that stored information relevant to the skills of our employees and the project we managed. We solved the value stream for the second cycle and defined a process for the skill matrix and project complexity tool. My collaborators and I focused on assessing the data and came up with baseline analytics from the skills matrix and project complexity tool. We used the assessment results to develop recommendations to reorganize our team project's assignments and improve the training plans for our employees. Our intervention will guide our organization to provide a better working experience for our employees and an opportunity to transform our organization's workforce operating model through increased usage of available digital technologies. Keywords: Information Technology and Business Process Management, Microsoft Power Apps/SharePoint, Agile Project Management Methodology, Design Thinking, and Information Technology Infrastructure Library (ITIL V4)